A causal relationship between uric acid and diabetic macrovascular disease in Chinese type 2 diabetes patients: A Mendelian randomization analysis. (1st July 2016) - Yan, Dandan; Wang, Jie; Jiang, Feng; Zhang, Rong; Wang, Tao; Wang, Shiyun; Peng, Danfeng; He, Zhen; Chen, Haibing; Bao, Yuqian; Hu, Cheng; Jia, Weiping
Abstract: Background: As the association between uric acid and macrovascular disease has been heavily debated, we aimed to confirm whether there is a causal relationship between uric acid and diabetic macrovascular disease through Mendelian randomization analysis. Methods: In 3207 type 2 diabetes patients, seventeen SNPs (single nucleotide polymorphisms) related to uric acid were genotyped. A weighted GRS (genetic risk score) was calculated using selected SNPs and the strength of their effects on uric acid levels. Diabetic macrovascular disease was diagnosed through vascular ultrasound, magnetic resonance imaging or other clinical evidence. Associations of diabetic macrovascular disease with uric acid and weighted GRS were evaluated separately. Results: In total participants and among females, the prevalence of diabetic macrovascular disease was significantly higher in hyperuricemic group than in normouricemic group, and uric acid was associated with diabetic macrovascular disease (OR = 1.068, p  = 0.0349; OR = 1.122, p  = 0.0158). The prevalence of diabetic macrovascular disease increased with the weighted GRS in a J-shaped manner for the females. The weighted GRS was positively correlated with uric acid in total population, male patients and female patients (β = 0.203, p  < 0.0001; β = 0.255, p  < 0.0001; β = 0.142, p  < 0.0001, respectively). The weighted GRS was significantly associated with diabetic macrovascular disease in female patients (OR = 1.184, p  = 0.0039). Among females, the observed association between weighted GRS and diabetic macrovascular disease was greater than predicted. Conclusions: Using the uric acid-related weighted GRS as an instrumental variable for Mendelian randomization analysis, our study provided an evidence for causal relationship between uric acid and diabetic macrovascular disease in Chinese females with type 2 diabetes mellitus. Highlights: Association between uric acid and macrovascular disease has been heavily debated. Mendelian randomization is a useful instrument to verify casual relationship. The role of uric acid in diabetic macrovascular disease is certified. It is a useful guidance for treatment of diabetic macrovascular disease.